Prickly Pear Betalain-Rich Extracts as New Promising Strategy for Intestinal Inflammation: Plant Complex vs. Main Isolated Bioactive Compounds - Smeriglio, A.; De Francesco, C.; Denaro, M.; Trombetta, D. (Frontiers in Pharmacology, 2021)
Recently, many studies have highlighted the health effects of betalains beyond their use as food dyes. The present study investigated betalain-rich extracts with different colors and their main bioactive compounds in order to provide first evidence as a new promising strategy for intestinal inflammation management. Prickly pear betalain–rich extracts, obtained by a QuEChERS method, have been characterized by LC-DAD-ESI-MS/MS analysis. The potential role of betanin, indicaxanthin, and prickly pear extracts in counteracting the antioxidant and anti-inflammatory events was evaluated by several in vitro cell-free and cell-based assays. Indicaxanthin and betanin represent the most abundant compounds (≥22.27 ± 4.50 and 1.16 ± 0.17 g/100 g dry extract, respectively). Prickly pear extracts showed the strongest antioxidant and anti-inflammatory activities with respect to the pure betalains both on in vitro cell-free and cell-based assays, demonstrating the occurrence of synergistic activity, without any cytotoxicity or alteration of the barrier systems. The release of reactive oxygen species (ROS) and key inflammatory markers (IL-6, IL-8, and NO) was strongly inhibited by both betalains and even more by prickly pear extracts, which showed a similar and sometimes better profile than the reference compounds trolox and dexamethasone in counteracting the IL-1β–induced intestinal inflammation.